INFLUENCE OF PARAMETERS OF CRYSTALLIZATION ON MODIFYING OF AN ALLOY - V. Yu. Stetsenko (Литьë и металлургия, 2015)
It is shown that extent of modifying of an alloy is proportional to overcooling at its hardening, viscosity of fusion and interphase superficial energy of crystals of the leading phase. The key technological parameters of modifying of an alloy are the speed of its hardening, viscosity of fusion and extent of refinement from surface-active elements. Their adsorption on crystals of the leading phase interferes with modifying of an alloy.